2019
DOI: 10.1177/2055207619868550
|View full text |Cite
|
Sign up to set email alerts
|

Designing technology tools to support engagement in mindfulness-based interventions: an analysis of teacher and student experiences

Abstract: Standard mindfulness-based interventions have significant at-home assignments of formal mindfulness practice as a key component. Engagement with formal home practice has been correlated with treatment outcomes, but participants often complete less than the assigned amounts. Here, we explore the requirements for technology tools that can support and encourage home practice, in a way that is appropriate and consistent with the core principles of mindfulness-based interventions. Interviews were held with a group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…e-learning or sharing portals), multimedia resources, the internet and video conferencing [1]. Students receive the content from teacher and communicate with the teacher via the same technologies and not in face to face setting [2,3]. A VLE is defined as a computer-based environment that is a relatively open system, allowing interactions and encounters with other participants and providing access to a wide [4].…”
Section: Introductionmentioning
confidence: 99%
“…e-learning or sharing portals), multimedia resources, the internet and video conferencing [1]. Students receive the content from teacher and communicate with the teacher via the same technologies and not in face to face setting [2,3]. A VLE is defined as a computer-based environment that is a relatively open system, allowing interactions and encounters with other participants and providing access to a wide [4].…”
Section: Introductionmentioning
confidence: 99%
“…Second, it is possible that participants pressed play on the guide within the smartphone app but did not actually listen to the guides. For instance, one participant in our user-centered design group suggested that she might cheat by pressing play on the recording and leave the phone while she engaged in other tasks [19]. We cannot exclude such a possibility.…”
Section: Limitations Of the Smartphone-monitoring Approach And This Studymentioning
confidence: 99%
“…In this exploratory study, we aimed to examine participant practice behavior during an 8-week MBSR program. We used a custom-developed app [19] that was designed to provide a simple user experience that did not conflict with any of the principles underpinning MBSR (eg, evaluating practice time as good or bad). We aimed to assess the number of practice sessions participants completed, the time of day participants practiced at, and the consistency of practice time.…”
Section: Self-reports Missing Data and The Timing Of Practicementioning
confidence: 99%
See 1 more Smart Citation
“…[31]). As gathering home practice logs proved difficult (a recurrent problem even in well-established MBCT for depression research [101][102][103][104][105]), the use of technology such as apps (which would automatically log patients accessing mindfulness meditation practices) would aid research into engagement in MBIs for OCD [105]. Similarly, it would be beneficial to include post-treatment questionnaires eliciting the extent of home practice.…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%